IMPLEMENTASI FUNGSI MANAJEMEN DALAM PERUMUSAN MANAJEMEN PENDIDIKAN DI SMKN 1 CIJULANG - Neneng Nurmalasari; Faishal Mas’ud; Imas Masitoh (JURNAL ILMIAH EDUNOMIKA, 2022)
Departing from Fathul Maujud's research in the The Implementation of Management Functions at Islamic Education Institutions (Case Study of Islahul Muta’allim Islamic Elementary School [MI] Management of Pagutan), researcher saw that similar research could be done in different types of schools. Therefore researchers are interested in conducting such research in vocational high schools. This research is intended to find out how principals implement four management functions according to George R. Terry, in the process of drafting a school management system. That is, planning, organizing, actuating, and controlling. The study was conducted using a qualitative approach and using interview, observation, and documentation methods for collecting data. The data obtained was analyzed using interactive models such as those developed by Miles and Huberman (1994). The research was conducted at state vocational high school 1 Cijulang, Cijulang District of Pangandaran Regency of West Java Province. The results of the study are: 1) The principal acted as the initiator and director in the management system in the school. 2) The principal used 4 management functions according to George R. Terry's theory. 3) The principal created the school's development team as an "accomplice" in the development of the school's management system. 4) The principal carried out an evaluation of the system that has been created. 5) The school management system produced "fruit" in the form of a program called Axioo Class Program. It is expected that from this research readers can implement management functions in their respective educational institutions. Keywords : Implementation, Management Function, Education Management.